Off the waterfront: the long-run impact of technological change on dock workers - El-Sahli, Zouheir; Upward, Richard (Wiley, 2017)
We investigate how individual workers and local labour markets adjust over a long time period to a discrete and plausibly exogenous technological shock, namely the introduction of containerisation in the UK port industry. This technology, which was introduced rapidly between the mid-1960s and the late-1970s, had dramatic consequences for specific occupations within the port industry. Using longitudinal micro-census data we follow dock-workers over a 40 year period and examine the long-run consequences of containerisation for patterns of employment, migration and mortality. The results show that the job guarantees negotiated by the unions protected dock-workers' employment until the guarantees were removed in 1989. A matched comparison of workers in comparable unskilled occupations reveals that, even after job guarantees were removed, dock-workers did not fare worse than the comparison group in terms of their labour market outcomes. Our results suggest that job guarantees provided a safety net which reduced the cost to workers of sudden technological change.